Land of the falling "poison pill" understanding defensive measures in Japan on their own terms - KOH, Alan K. (Institutional Knowledge at Singapore Management University, 2020)
Embraced by United States ("U.S.") managers in the 1980s as a lifeline in a sea of hostile takeovers, the poison pill fundamentally altered the trajectory of American corporate governance. When a hostile takeover wave seemed imminent in Japan in the mid-2000s, Japanese boards appeared to embrace this American invention with equal enthusiasm. Japan's experience should have been a ringing endorsement for the utility of American corporate governance solutions in foreign jurisdictions -but it was not to be. Japan's unique interpretation of the "poison pill" that was so eagerly adopted by Japanese companies in the mid-to-late 2000s has turned out to be nothing like their potent American namesakes - and, in fact, the opposite of what would be expected by leading U.S. academics who have built a cottage industry publishing on the U.S. poison pill.Based on hand collected empirical data, we provide the first indepth analysis of why Japan's "poison pill" (defensive measures) is heading towards extinction- a watershed reversal that is unexplained in the Japanese literature and has almost entirely escaped the English language literature. By drawing on our hand-collected data, case studies, and Japanese jurisprudence, we illuminate the unique and untold story of how one of the most discussed mechanisms of corporate governance in the U.S. has worked almost entirely differently when transplanted to Japanese soil-the importance of which is heightened as Japan is by far the largest economy in which the poison pill has been tested outside of the United States. Additionally, our analysis sheds light on the unexpected importance of Japan's recently implemented corporate governance code and stewardship code-two Western legal transplants that have garnered considerable attention in the English language literature, but which have yet to be evaluated in light of their impact on defensive measures in Japan.